Short-term effects on physical activity level with web-based self-management support in people with COPD: a randomised controlled trial - Tobias Stenlund; Åsa Karlsson; Per Liv; André Nyberg; Karin Wadell (npj Primary Care Respiratory Medicine)
Abstract We aimed to evaluate short-term effects of a web-based self-management support on objectively measured physical activity (PA) compared to usual care in people with chronic obstructive pulmonary disease (COPD). We conducted a pragmatic randomised controlled trial including people with stable COPD within primary healthcare. Participants were randomised to intervention group, IG (access to the COPD Web, an interactive website to support self-management with focus on PA), or to control group, CG (usual care). Primary outcome at 3 months was change in accelerometry-measured daily steps analysed with ANCOVA, and secondary outcomes were self-reported PA, disease-related symptoms, and quality of life. Missing data in intention-to-treat (ITT) analyses were multiply imputed. One hundred and forty-six participants (n = 73/group), mean (SD) age 69.5 (6.7) years, FEV1pred 60.7 (19.1)% were included. The ITT analysis showed no significant difference in steps between the groups: 1295 steps (95% CI: [−365, 2955], p = 0.12), while the complete case analysis (n = 98) revealed a significant difference of 1492 steps (95% CI: [374, 2609], p = 0.01) in favour of IG. A significant increase in self-reported PA was seen in IG in both the ITT and complete case analysis. In summary, access to the COPD Web was insufficient to increase short-term PA level compared to usual care. However, among participants with complete step data, a clinically relevant effect on daily steps exceeding the minimal important difference was observed, partly explained by higher baseline PA than among dropouts. This indicates that access to the COPD Web may increase PA levels for some people with COPD.